Individualized employee engagement or collaborative employee relations: insights on leadership strategies to manage employees in the UK market - Sourav Mohanty (Problems and Perspectives in Management, 2018)
Leadership can be defined as the ability of an individual to lead or guide other people, teams or organizations. There have been many theories related to this topic including the characteristics of leaders, their situational communication, purpose, performance, authority, vision and mission, charm and presence of mind. The main types of employee engagement discussed in this study are individualized employee engagement and collaborative employee engagement in the context of the UK. This study mainly seeks to investigate the insights of employees and leaders on different leadership strategies to manage employees in the UK-based MNCs. Descriptive and inferential analysis was performed so as to ascertain the influence of two different leadership strategies – Individualized Employee Engagement (IEE) and Collaborative Employee Relations (CER) – on effective employee management. It was validated from findings in this study that employees and leaders both prefer and believe that individualized employee engagement leads to better and effective employee management.